BAGURAU: MINANGKABAU ORAL LITERATURE IN LUHAK NAN TIGO WEST SUMATRA - Anwar, Khairil; Cika, I Wayan; Kutha Ratna, I Nyoman; Weda Kusuma, I Nyoman (e-Journal of Linguistics; Vol. 4. Juli 2010 No. 2, 2010)
This research presents the results of analysis and the description of severalproblems related to the oral literary work of Bagurau which have not beencompletely and deeply analyzed by previous researchers. The problems are related tothe oral literary text of Bagurau. In line with the problems discussed, qualitativemethod with sociological approach is applied in this study. This means that theresearch was initiated by comprehending the data and then the theory ofdeconstruction, that is, the theory of “trace” functions and the theory ofhypersemiotics were chosen for analyzing the data. The theories were observed insuch a way that they could be synthesized into one theory or a novelty.The description of the results of analysis was initiated by presenting thesocial context of Bagurau which was then continued with the forms of the textincluding the construction of the text with regard to its scheme, communicativepattern, formulas, sound elements, style, diction, theme, characters and setting. Basedon the deconstruction pattern introduced by Derrida, as far as the text of Bagurau isconcerned, several new forms of text have been found developing. They are theforms of parody, schizophrenia, kitsch, pastiche, hybrid, eclectic, and nonsense.Based on what has been traced, the text of Bagurau used to function as amusement toexpress joy, production and reproduction of local culture, expression, representation,economy, introspection, and togetherness. Then the meanings which have been foundare the meanings of pluralism, egalitarianism, emancipation, democracy, theideology of parewa, destruction of phallocentrism, solidarity, social control, and self- esteem - embarrassment.
Keywords: Bagurau oral literature, text, plurality, deconstruction